The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1038/sj.leu.2404500
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification for survival and leukemic transformation in essential thrombocythemia: a single institutional study of 605 patients

Abstract: Unlike the case with thrombosis, prognostic models for survival and leukemic transformation (LT) in essential thrombocythemia (ET) are not available. Among 605 patients with ET seen at our institution and followed for a median of 84 months, 155 died and LT was documented in 20 patients (3.3%). In a multivariable analysis, hemoglobin level below normal (females o120 g/l; males o135 g/l) was identified as an independent risk factor for both inferior survival and LT. Additional risk factors for survival included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 29 publications
8
121
1
3
Order By: Relevance
“…As only 17% were in high risk in one prior USA study (Gangat et al, 2007). Compared with data from developed countries, majority of our patients (57.1%) were in high risk.…”
Section: Discussioncontrasting
confidence: 60%
“…As only 17% were in high risk in one prior USA study (Gangat et al, 2007). Compared with data from developed countries, majority of our patients (57.1%) were in high risk.…”
Section: Discussioncontrasting
confidence: 60%
“…In the same study, risk factors for fibrotic transformation included prefibrotic PMF morphology, advanced age, and anemia although the presence of JAK2V617F was associated with a lower risk of fibrotic transformation [52]. Using age 60 years, hemoglobin below normal value and leukocyte count >15 3 10 9 /L, one study demonstrated a median survival of >20 years in the absence of all three risk factors and 9 years in the presence of two of the three risk factors [54].…”
Section: Risk Factors For Survival and Leukemic Or Fibrotic Transformmentioning
confidence: 90%
“…There are, to date, no controlled studies that implicate either hydroxyurea or busulfan as being leukemogenic in either ET or PV. Similarly, the two largest non-controlled studies in ET [54] and PV [108] do not support the concern that leukemia might arise from the use of hydroxyurea and there is additional evidence to that effect from long-term studies of patients receiving hydroxyurea for sickle cell disease [123]. The evidence for busulfan leukemogenicity in the context of treatment for PV or ET is equally weak and inappropriately extrapolated from older patients with advanced phase disease and exposed to multiple cytoreductive drugs.…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 99%
“…[69][70][71][72] By contrast, a leukemogenic potential of hydroxyurea (HU) has not been shown in clinical trials, although there is evidence showing that the sequential use of HU and other cytoreductive drugs (alkylating agents, radioactive phosphorus) increases the risk of AL/MDS. [72][73][74][75] In addition, several retrospective studies did not find an increased risk of AL in PV and ET treated with HU alone, [76][77][78] and similar conclusions were drawn from a recent meta-analysis of HU therapy in sickle cell anemia. 79 Still, very long-term results of prospective studies in HU-treated MPN patients with more than 10 years of follow-up showed a cumulative incidence of AL/MDS of more than 10% beyond 12 years of follow-up, suggesting that the risk of leukemic evolution could be higher than reported earlier in studies with shorter follow-up.…”
Section: Ifn-a and Leukemic Evolutionmentioning
confidence: 76%